Features of pathogenesis of a chronic stomalgia (Эндодонтия Today)
Based on the information-structural theories of pain and clinical and physiological studies have examined the pathogenesis of chronic stomalgia, selected clinical and pathogenetic variants of chronic stomalgia: somatogenic (nociceptive), neurogenic (neuropathic), and psychogenic disregulation and integrative.